Security community building? : an assessment of Southern African regional integration in the post-apartheid era - Lekhooa, Tumo (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
The thesis traces Southern African security dimensions from the Cold War and the period of apartheid in South Africa to the post-apartheid era. It makes an attempt to investigate the prospects of Southern Africa becoming a security community and the processes and practices underlying these efforts. Using the constructivist theory approach to international relations, the thesis argues that the preoccupation with principles of sovereignty and non-interference, a lack of political will and the absence of common values that could help SADC institute binding rules and decision-making are the main blocks that prevent the region from asserting itself as a security community. All these militate against the idea of mutual accountability among SADC member states and have a negative impact on the institutional and functional capacity of SADC. This also prevents SADC from dealing with the emerging non-military human security threats in the region. In consideration of this, the thesis argues that the idea of security community building in Southern Africa remains not only a regional issue, but also requires the involvement of extra-regional actors.
Keywords: South Africa -- Politics and government -- 1994-; Africa, Southern -- Economic integration; National security -- Africa, Southern; Political stability -- Africa, Southern; Southern African Development Community